Immunogenicity and safety of a quadrivalent plant-derived virus like particle influenza vaccine candidate—Two randomized Phase II clinical trials in 18 to 49 and ≥50 years old adults - Pillet, Stéphane; Couillard, Julie; Trépanier, Sonia; Poulin, Jean-François; Yassine-Diab, Bader; Guy, Bruno; Ward, Brian J.; Landry, Nathalie (PloS one, 2019)
New influenza vaccines eliciting more effective protection are needed, particularly for the elderly who paid a large and disproportional toll of hospitalization and dead during seasonal influenza epidemics. Low (≤15 μg/strain) doses of a new plant-derived virus-like-particle (VLP) vaccine candidate have been shown to induce humoral and cellular responses against both homologous and heterologous strains in healthy adults 18-64 years of age. The two clinical trials reported here addressed the safety and immunogenicity of higher doses (≥15 μg/strain) of quadrivalent VLP candidate vaccine on 18-49 years old and ≥50 years old subjects. We also investigated the impact of alum on the immunogenicity induced by lower doses of the vaccine candidate. In the first Phase II trial reported here (NCT02233816), 18-49 year old subjects received 15, 30 or 60 μg/strain of a hemagglutinin-bearing quadrivalent virus-like particle (QVLP) vaccine or placebo. In the second trial (NCT02236052), ≥50 years old subjects received QVLP as above or placebo with additional groups receiving 7.5 or 15 μg/strain with alum. Along with safety recording, the humoral and cell-mediated immune responses were analyzed. Local and systemic side-effects were similar to those reported previously. The QVLP vaccine induced significant homologous and heterologous antibody responses at the two higher doses, the addition of alum having little-to-no effect. Serologic outcomes tended to be lower in ≥50 years old subjects previously vaccinated. The candidate vaccine also consistently elicited both homologous and heterologous antigen-specific CD4+ T cells characterized by their production of interferon-gamma (IFN-γ), interleukine-2 (IL-2) and/or tumor-necrosis factor alpha (TNF-α) upon ex vivo antigenic restimulation. Overall, the 30 μg dose produced the most consistent humoral and cellular responses in both 18-49 and ≥50 years old subjects, strongly supporting the clinical development of this candidate vaccine. That particular dose was chosen to test in the ongoing Phase III clinical trial.